Metagenomic Investigation of Torque Teno Mini Virus-SH in Hematological Patients - Bal, Antonin; Oriol, Guy; Josset, Laurence; Generenaz, Laurence; Sarkozy, Clémentine; Sesques, Pierre; Salles, Gilles; Morfin, Florence; Lina, Bruno; Becker, Jérémie; Reynier, Frédéric; Mallet, François; et al. (Frontiers in Microbiology, 2019)
A new member of Anelloviridae, named torque teno mini virus (TTMV)-SH, was recently identified in the serum of three Hodgkin’s lymphoma patients suggesting that TTMV-SH may be associated with this type of hematological malignancy. We investigated by metagenomic analysis the presence of TTMV-SH-related viruses in plasma samples (n = 323) collected from patients with various hematological malignancies (multiple myeloma (MM, n = 256), non-Hodgkin’s lymphoma (NHL, n = 20), acute myeloid leukemia (n = 10)) and from healthy donors (n = 37). TTMV-SH-related strains were identified in 24 samples corresponding to four MM and one NHL patients. Phylogenic analysis revealed that the 24 isolates were close to the TTMV-SH strains previously identified, sharing 79.6–86.7% ORF1 nucleotide sequence identity. These results suggest that TTMV-SH-related viruses might be found in hematological diseases other than Hodgkin’s lymphoma. Due to the high genetic variability within Anelloviridae species, the association between a particular medical condition and a new genotype should be interpreted with caution.